"Togetherness:" the role of intergenerational and cultural engagement in urban American Indian and Alaskan Native youth suicide prevention. Issue 1 (4th March 2021) - Doria, Celina M.; Momper, Sandra L.; Burrage, Rachel L.
ABSTRACT: In a collaborative study with an Urban Indian Health Organization (UIHO) and a University, we conducted six talking circles over three years with American Indian and Alaskan Native (AI/AN) elders, adults, and youth to examine perceptions of suicide and suicide prevention strategies within their community. Results of a thematic analysis indicated that normalization of suicide, stigma, and historical trauma were barriers to suicide prevention. Consistent themes of elders, adults, and youth over all three years reflected the need for intergenerational engagement and cultural connectedness as suicide prevention strategies. Implications for culturally-grounded social work practice with AI/ANs are presented.